2016
DOI: 10.52321/geolbalc.45.0.47
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal and metalloid mobilisation and rates of contamination of water, soil and bottom sediments in the Chiprovtsi mining district, Northwestern Bulgaria

Abstract: Geochemical studies of seasonally collected mine, stream and drinking waters, bottom sediments (mine and stream) and soil samples from all mining sections were carried out in order to assess the rates of pollution in the immediate proximity to underground mining facilities and related waste rock dumps. The determined concentrations of studied elements in water (As, Pb, Cu, Zn and Sb) show spatial distribution corresponding to ore mineralisation in different sections. Arsenic concentrations show gradual decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…The PC3 map presents a spatial distribution of elevated factor scores regions coinciding with the ore deposits in Bulgaria, mainly copper, lead–zinc and polymetallic ores ( Figure 4 ). Dimitrova et al [ 40 ] reported higher concentrations of Cu, Zn, As and Pb in northwestern Bulgarian soils caused by mining activities in the region. It has already been mentioned that the largest mining areas are in the central Rhodope zone, the western part of the Balkan zone and the eastern part of the Srednogorie zone, but unexploited ore deposits are also located in the southern central part of the Moesian platform [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PC3 map presents a spatial distribution of elevated factor scores regions coinciding with the ore deposits in Bulgaria, mainly copper, lead–zinc and polymetallic ores ( Figure 4 ). Dimitrova et al [ 40 ] reported higher concentrations of Cu, Zn, As and Pb in northwestern Bulgarian soils caused by mining activities in the region. It has already been mentioned that the largest mining areas are in the central Rhodope zone, the western part of the Balkan zone and the eastern part of the Srednogorie zone, but unexploited ore deposits are also located in the southern central part of the Moesian platform [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Además, se realizaron análisis estadísticos multivariados como el análisis de componentes principales (ACP), haciendo uso de la librería FactoMineR (Lê et al 2008) y el análisis de correspondencia canónica (ACC) utilizando la librería Vegan (Oksanen et al 2019). Los datos físicos y químicos de las minas fueron recolectados de los estudios individuales de cada mina y recomendamos revisarlos a profundidad para conocer sus detalles metodológicos (Aguinaga et al 2018, Dimitrova et al 2016, Pakostova et al 2020, Ettamimi et al 2019, Rodrigues et al 2014, Li et al 2019.…”
Section: Procesamiento Estadísticounclassified